Donors' experiences and attitudes of fecal microbiota transplantation: An empirical bioethics study from China. Issue 4 (21st November 2022) - Ma, Yonghui; Ke, Dawei; Li, Danyi; Zhang, Quan
Abstract : Donor participation is a critical part of ensuring the development of human microbiome research and the clinical application of fecal microbiota transplantation (FMT). Most FMT donors are still not sufficiently aware of the risks associated with the act of donating gut microbiota, especially the risk of data privacy disclosure. Enhanced awareness of the moral responsibility of the researchers and ethical oversight by ethics committees are needed.